FoxO1 Overexpression Ameliorates TNF-α-Induced Oxidative Damage and Promotes Osteogenesis of Human Periodontal Ligament Stem Cells via Antioxidant Defense Activation. (31st October 2019) - Huang, Xiaojun; Chen, Huan; Xie, Yunyi; Cao, Zeyuan; Lin, Xuefeng; Wang, Yan
Abstract : Periodontitis is a chronic disease that includes the pathologic loss of periodontal tissue and alveolar bone. The inflammatory environment in periodontitis impairs the osteogenic differentiation potential and depresses the regeneration capacity of human periodontal ligament stem cells (hPDLSCs). Since Forkhead box protein O1 (FoxO1) plays an important role in redox balance and bone formation, we investigated the role of FoxO1 in oxidative stress resistance and osteogenic differentiation in an inflammatory environment by overexpressing FoxO1 in hPDLSCs. First, we found that FoxO1 overexpression reduced reactive oxygen species (ROS) accumulation, decreased malondialdehyde (MDA) levels, and elevated antioxidant potential under oxidative condition. Next, the overexpression of FoxO1 protected hPDLSCs against oxidative damage, which involved stabilization of the mitochondrial membrane potential. Third, overexpressed FoxO1 promoted extracellular matrix (ECM) mineralization and increased the expression of the osteogenic markers Runx2 and SP7 in the inflammatory environment. These results indicated that FoxO1 overexpression in hPDLSCs has an anti-inflammatory effect, increases antioxidative capacity, and positively regulates osteogenesis in a mimicked inflammatory environment.